Research on the Training Mode of Innovative Talents in Information and Computing Science from the Perspective of Scientific and Technological Innovation - Jing Lei; Jia-Qing Song; Ji-Yan Wang (Ilmu Inovasi Nusantara, 2024)
This study aims to identify and analyze effective training modes for fostering innovative talents in information and computing science, with a focus on the perspective of scientific and technological innovation. The research method employed includes a comprehensive literature review, interviews with industry experts and academics, and empirical data analysis from existing training programs. The findings indicate that an integrated approach combining project-based learning, interdisciplinary collaboration, and practical experiences can enhance students' innovative capabilities. Recommendations from this research include the need for increased investment in educational facilities and resources, the formation of strategic partnerships between universities and industries, and the development of curricula responsive to the evolving needs of the job market. This research provides a significant contribution to the development of relevant and effective training strategies in response to societal demands for innovative talents in the field of information and computing science